Latin America and the Rising South : Changing World, Changing Priorities - de la Torre, Augusto (Washington, DC: World Bank, 2015)
The world economy is not what it used to be twenty years ago. For most of the 20th century, the world economy was characterized by developed (North) countries acting as 'center' to a 'periphery' of developing (South) countries. However, the recent rise of developing economies suggests the need to go beyond this North-South dichotomy.